Effect of deep freezing of Phytophtora infestans on their survival and pathogenicity - Sobkowiak, Sylwester; Zarzycka, Hanna; Zimnoch-Guzowska, Ewa (Plant Breeding and Seed Science, 2004)
The maintenance of Phytophthora infestans cultures isolates from blighted potato, frozen in liquid nitrogen, was studied in two experiments. The effects of deep freezing and acclimatization pre-treatment at different temperatures on culture survival and stability of virulence and aggressiveness were evaluated. The best survival of cultures maintained for three months in liquid nitrogen was expressed, when cultures were acclimatized before freezing at 7˚C. The survival of frozen cultures was significantly worse in comparison with control combinations stored on rye-agar and rye-agar under paraffin oil for short time (in experiment I – 40 days, in experiment II – three months). The virulence spectrum of frozen cultures after thawing was more narrow than that one observed before culture freezing. However this virulence spectrum did not differ significantly from virulence range of control cultures. The level of aggressiveness of culture stored in liquid nitrogen did not differ significantly from control cultures as well. The virulence spectrum and aggressiveness level of cultures frozen in liquid nitrogen were significantly higher after two passages of thawed cultures on potato tissues than after single passage.